Implementasi Kewajiban Orang Tua dalam Pemenuhan Hak Anak: Studi Kasus di Desa Banjaran Godang Berdasarkan Kompilasi Hukum Islam dan UU Perlindungan Anak - Ramadhan, Ahmad Syuqrun; Lubis, Azwani (Fakultas Hukum, Universitas Muslim Indonesia, 2024)
This research aims to examine the implementation of parental obligations in Banjaran Godang Village in fulfilling children’s rights, specifically the right to education, play, and growth and development, based on the Compilation of Islamic Law and the Child Protection Law. This study adopts a combined approach, namely qualitative with the field research method and normative, by analyzing data qualitatively to describe the problem and answer the research objectives. The results showed that implementing parental obligation in fulfilling children’s rights in Banjaran Godang Village is not fully aligned with the Compilation of Islamic Law and Child Protection Law. There is a misunderstanding among parents who consider formal education merely Sunnah and prioritize trading and farming skills, based on their interpretation of the life of the Prophet Muhammad SAW in his childhood. As a result, children’s rights to play, grow, and develop are neglected. Therefore, it is recommended that the Banjaran Godang Village Government develop a comprehensive and sustainable counseling and outreach program regarding children’s rights and parental obligations. This program should involve religious leaders to correct misunderstandings about formal education in Islam, experts in the field of child protection to provide a comprehensive understanding of children’s rights, and related institutions to optimize program implementation.